Renewable Energy Deployment as a Pathway to Sustainability and the Sustainable Development Goals (SDGs): A Review - Yoshihiro Hamaguchi (Ekonomikalia Journal of Economics, 2026)
The energy transition from fossil fuels to renewable energy is underway to achieve a sustainable society based on carbon neutrality. However, there is an ongoing debate about how the implementation of such energy technologies will affect sustainability (social, economic, and environmental aspects). This review outlines research trends on the effects of renewable energy deployment on sustainability from the perspectives of income inequality, energy inequality, human capital, energy education, gender, health, and community, focusing on high-profile papers for the period 2014-2024. Renewable energy and income inequality are negatively related, and promoting renewable energy innovation through R&D subsidies is expected to decarbonize and alleviate poverty. Human capital promotes decarbonization through the diffusion and consumption of renewable energy, but in some cases, the effects are not apparent. However, energy education can be effective in addressing human capital shortages in the renewable energy sector. Gender inequality and energy inequality are closely linked, with women with poor energy access suffering health problems due to smoke pollution from cooking. Women's participation in society will encourage the spread of renewable energy and improve health standards. Local communities with voluntary citizen participation, rather than state initiative, are expected to be the actors that encourage decarbonization through renewable energy.